2010
DOI: 10.1111/j.1365-2222.2010.03636.x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary adenylate cyclase‐activating peptide receptor 1 mediates anti‐inflammatory effects in allergic airway inflammation in mice

Abstract: Summary Background Bronchial asthma is characterized by airway inflammation and reversible obstruction. Since the gold standard of therapy, a combination of anti-inflammatory corticosteroids and bronchodilatory β2 agonists, has recently been discussed to be related to an increased mortality, there is a need for novel therapeutic pathways. Objective A new experimental concept that encompasses the vasoactive intestinal peptide/pituitary adenylate cyclase activating peptide (PACAP) family of receptors by demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Interestingly, the VPAC1 related receptor PAC1 was recently shown to be differentially expressed in a murine model of ovalbumin-induced asthma [17]. In this study an increased PAC1R mRNA expression was present in lung tissue under allergic conditions.…”
Section: Resultssupporting
confidence: 54%
“…Interestingly, the VPAC1 related receptor PAC1 was recently shown to be differentially expressed in a murine model of ovalbumin-induced asthma [17]. In this study an increased PAC1R mRNA expression was present in lung tissue under allergic conditions.…”
Section: Resultssupporting
confidence: 54%
“…After induction of experimental asthma, MS rats had greater number of eosinophils in broncho-alveolar lavage than controls or HA rats (P =0.002). In HA rats, induction of experimental asthma was associated with markedly increased levels of adreno-corticotropin compared with the MS or control groups (P for one-way analysis of variance=0.02) 47 . Taken together, these results suggest that early post-natal stressors have effects on the “neuroendocrine immune system” lasting into adult life.…”
Section: Stress Immune Responses and Asthmamentioning
confidence: 95%
“…However, the biological plausibility of our results is supported by experimental models showing that PACAP acts as endogenous bronchodilator, relaxing airway smooth muscle 44,45 . Moreover, PACAP protects against endotoxin-induced allergic airway inflammation (AAI) in rodents 46 , in which the PAC1 receptor mediates anti-inflammatory effects in AAI 47 . Together with these experimental findings, our results suggest that genetic and epigenetic variation in a susceptibility gene for PTSD and childhood anxiety ( ADCYAP1R1 ) is implicated in the pathogenesis of asthma in children disproportionately exposed to violence or traumatic events, such as Puerto Ricans.…”
Section: Genetics Genomics and Epigenetics Of Stress And Asthmamentioning
confidence: 99%
“…However, the study performed by Lauenstein et al, (2011) suggested that PAC1 receptor mediates anti-inflammatory effects in allergic airway inflammation. Thus, PAC1 receptor agonists may be a promising candidate in airway allergic diseases such as bronchial asthma [53]. …”
Section: General Characteristics Of Vasoactive Intestinal Peptide mentioning
confidence: 99%